Social Enterprises Within the Public Sector’s Purview: A Taxonomy-Based Study on South Korea - Claassen, Casper Hendrik; Mair, Johanna; Bidet, Eric (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2024)
This study applies a hierarchical clustering approach to identify social enterprise models that have appeared in a setting of public sector-led incubation. Within such a context, a high degree of conformity ought to be apparent due to the coercive isomorphic pressures associated with public sector patronage. We nominate South Korea for our analysis, given that the rising number of social enterprises in the country is closely related to a regulatory intervention. Based on an analysis of 468 social enterprises, we find, contrary to expectations, that distinct clusters of government-certified social enterprises have emerged, namely social utility niche, job outsourcing, market opportunity, and integrated balanced models. We typologize these models according to their strategic orientation, mission focus, and institutional alignment. In doing so, we contribute to social enterprise research by illustrating how organizational pluralism may manifest when the growth of a population of social enterprises is directly linked to public sector intervention and regulation.